2011
DOI: 10.1016/j.genm.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular-Renal and Metabolic Characterization of a Rat Model of Polycystic Ovary Syndrome

Abstract: Background Polycystic ovary syndrome (PCOS) is the most common reproductive dysfunction in premenopausal women. PCOS is also associated with increased risk of cardiovascular disease at the time of PCOS and later in life. Hypertension, a common finding in women with PCOS, is a leading risk factor for cardiovascular disease. The mechanisms responsible for hypertension in women with PCOS has not been elucidated. Objectives To characterize the cardiovascular-renal consequences of hyperandrogenemia in a female ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 54 publications
9
127
1
Order By: Relevance
“…As a model of human polycystic ovary syndrome, 10 weeks of DHT treatment starting during adolescence in female rats (13,14) induced significant arteriole alterations in our studies. We observed an increase in vascular diameter, a reduction of the Note: The 120-minute postload insulin level in the DHT group was significantly higher than in the control group (*P< .01).…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…As a model of human polycystic ovary syndrome, 10 weeks of DHT treatment starting during adolescence in female rats (13,14) induced significant arteriole alterations in our studies. We observed an increase in vascular diameter, a reduction of the Note: The 120-minute postload insulin level in the DHT group was significantly higher than in the control group (*P< .01).…”
Section: Discussionsupporting
confidence: 46%
“…It has been shown that an 8-12-week DHT treatment identical to the one that we used induces PCOS and significantly, approximately threefold, increases androgen levels in female rats (13). Yanes has detected several metabolic abnormalities (14). Despite normal E 2 levels, DHT-treated animals exhibited estrus cycle dysfunction.…”
Section: Sara Vascular Insulin Resistance In Pcos Fertil Steril 2012mentioning
confidence: 69%
See 3 more Smart Citations